SKEPTISME TERHADAP AGAMA DALAM FILSAFAT DAVID HUME ( 1711-1776) - Saidul Amin (Lembaga penelitian dan pengabdian kepada masyrakat, 2010)
History of Western civilization can not be separated from philosophy and religion. At first the philosophy was born as a force infantry to break thought the dogmas and ideas of superstition that has been ingrained in the public body. Then came the religion as a